The double nature of the price of gold—A quantitative analysis based on Ensemble Empirical Mode Decomposition. (March 2016) - Ming, Lei; Yang, Shenggang; Cheng, Cheng
Abstract: The research perspective of gold is either as a commodity or as a financial asset in most previous research. This paper initially examines the double nature of the price of gold both as a commodity and money from 1969 to 2014 by a statistics model, namely the Ensemble Empirical Mode Decomposition (EEMD). We decompose and categorize the gold price by time frequency into three different series: high frequency series, low frequency series and trend series, which takes 4.17%, 25.68%, 70.15% of the total variability, respectively. The high frequency series is consistent with the reaction of gold price to the influence of speculation and economic events, while the low frequency series is changing simultaneously with gold's varying role in world currency and as a safe haven asset. The trend series of gold grows steadily because of scarcity and increasing volume of jewelry purchases. Therefore, we interpret the high frequency series and trend series as a reflection of gold's commodity property, and the low frequency series is associated with gold's monetary property. This technology of EEMD sheds light on the double nature and price change of gold in the past. Highlights: We decompose and reconstruct the gold price into the high frequency, the low frequency and the trend series. The high frequency and trend series reflects gold׳s commodity property. The low frequency reflects gold׳s monetary property.